Expression and activity characterization of fatty acyl-CoA reductases in Saccharomyces cerevisiae - Lim, Pei Yu (2013)
Medium chain alkanes make up a huge fraction of gasoline that is widely used in land transportation today. Biosynthesis of alkanes from fatty acids was discovered in cyanobacteria and plants. Two enzymes, namely acyl-CoA reductase and aldehyde decarbonylase, catalyse this pathway with aldehyde as the intermediate. The aim of this project is to express and characterise acyl-CoA reductases. This would help to facilitate metabolic engineering of acyl-CoA reductases for fatty aldehyde production in S. cerevisiae. Six acyl-CoA reductase genes were selected for expression in Saccharomyces cerevisiae (S. cerevisiae). After cloning the reductase genes into S. cerevisiae, the yeast strain was analysed for fatty acyl-CoA reductase protein expression and activity. Gas chromatography-mass spectrometry (GC-MS) was used to detect the fatty aldehydes produced in vivo and in vitro. Fatty acids in the medium was shown to be readily uptaken and accumulated in S. cerevisiae. By comparing the respective peak areas, the ratio of C12 saturated fatty acid to C16 saturated fatty acid present in S. cerevisiae was increased more than 60 times from 0.09 to 6.39 through exogenous uptake of fatty acid. The expression of six FAR genes in S. cerevisiae was confirmed by Western Blot analysis. The activity of these expressed genes, however, was not detected in vivo and this could be due to competing pathways in S. cerevisiae for the consumption of fatty acids as S. cerevisiae contains aldehyde dehydrogenase (ALD) genes that catalyse the conversion of fatty aldehydes into fatty acids. In vitro studies were done by using crude lysate but fatty aldehyde was not detected. As a result, optimisation of purification process for FAR was carried out to remove intracellular proteins for activity assays but insufficient amount of FAR was obtained for the assay as most of the protein was expressed in the insoluble form.